THE MOVEMENT OF SHEIKH AHMAD YASIN AND THE MISSION OF PALESTINIAN LIBERATION: GERAKAN SYEIKH AHMAD YASIN DAN MISI PEMBEBASAN PALESTINA - Erawati, Dian; M. Thalal (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
This research aims to explore the activities of Sheikh Ahmad Yasin in the Islamic resistance movement (Hamas) in Palestine. The results reveal that Sheikh Ahmad Yasin, who founded Hamas in 1987, held a prominent position among the leaders of organization and was regarded as one of the significant figures of Palestinian martyrs. While serving as the leader of Hamas, Sheikh Ahmad Yasin played a pivotal role in the establishment of several institutions, including zakat collection agencies, peace institutions to resolve disputes among residents, Islamic schools, social institutions, and more. Hamas plays a role in Palestinian society for socialization, interaction, mobilization, and the liberation of Palestinian society from all conflicts and Israeli occupation. Sheikh Ahmad Yasin's movement has a profound and beneficial impact on Palestinian society, providing healthcare, education, and religious guidance to the population in the Gaza Strip, an area controlled by Palestine. It can be concluded that Sheikh Ahmad Yasin's movement and the mission of Palestinian liberation serve a crucial role in society for socialization, interaction, and realizing the struggle for independence through the Hamas movement.